Determinação de indicadores de sustentabilidade da bananicultura no Brejo Paraibano - Sousa, Davi Stefani (2018)
The fruit production has represented an important role in job generation and income in Paraiba State. The cultivation of the banana has become the main agricultural activity in the Microregion of Brejo Paraibano. To evaluate the sustentability indicators of its agricultural system, it was used data from Instituto Brasileiro de Geografia e Estatística (IBGE), since 2005 to 2015, field research – interviews and chemical and physical analysis of soils, and Sepúlveda methodology (2008), in 40 agricultural proprieties of Alagoa Nova and Bananeiras counties. It has been found that banana culture is dominating in harvested area, production value and gross monetary income, above all further cultures in Brejo, and the equations of regression of the linear model indicate significant decline in all analysed variables to the total crop, permanente crop and the banana culture. It has been found, yet, that, in the analysed counties, the soils showed themselves, for their texture and base saturation, respectively, favorably conditions to banana harvest and with appropriate fertility level, even it has presented low exchangeble potassium content e medium organic matter content. In spite of the favorably conditions, the sustentability indicators of sustentability of banana culture showed, in these two counties, index with instability level in socio-demographic and enviromental dimensions - enhancing public health problems and environmental disbalance, and index with critical level in economic and political-institutional dimensions - showing problems in the organizing and productive, commercial and technical-scientific integration of rural producers.